Iron and copper recovery from copper slags through smelting with waste cathode carbon from aluminium electrolysis - Mao, Kai-xuan; Li, Lei; Xu, Miao (Journal of Central South University, 2021)
To recover metal from copper slags, a new process involving two steps of oxidative desulfurization followed by smelting reduction was proposed in which one hazardous waste (waste cathode carbon) was used to treat another (copper slags). The waste cathode carbon is used not only as a reducing agent but also as a fluxing agent to decrease slag melting point. Upon holding for 60 min in air atmosphere first and then smelting with 14.4 wt% waste cathode carbon and 25 wt% CaO for 180 min in high purity Ar atmosphere at 1450 °C, the recovery rates of Cu and Fe reach 95.89% and 94.64%, respectively, and meanwhile greater than 90% of the fluoride from waste cathode carbon is transferred into the final slag as CaF 2 and Ca 2 Si 2 F 2 O 7 , which makes the content of soluble F in the slag meet the national emission standard. Besides, the sulphur content in the obtained Fe-Cu alloy is low to 0.03 wt%.